Available Natural Potentials for Exploiting Mineral Resources in Industrial Activity in the Kurdistan Region of Iraq (Journal of the College of Basic Education, 2026)
Mineral wealth is one of the most important pillars that can contribute to the development of industrial activity in the Kurdistan Region of Iraq, as it provides a fundamental base for many industries through the diverse raw materials and primary materials it offers. These resources are also considered an important pillar for scientific research and technical development in the fields of exploration, extraction, and processing. The region is characterized by the diversity of its mineral resources (metallic and non-metallic), making it rich in significant investment potential that has not been adequately exploited to date. Hence the importance of this research, as the study area is rich in ores and mineral raw materials necessary for developing industrial activity. The research also contributes to providing a reliable knowledge framework regarding the distribution of mineral resources and their potential, thereby enhancing strategic planning and decision-making for developing the industrial sector in the region. The research aims to study the reality of the industrial sector in the Kurdistan Region by analyzing the impact of natural factors on the distribution of industrial facilities and their spatial spread patterns, and highlighting the importance of mineral resources and their role in supporting industrial activity and enhancing its productive capacities. To achieve the study's objective, the research was divided into three main axes. The first axis addresses the theoretical framework of the study, including an introduction to the study area with reference to relevant concepts and terminology. The second axis focuses on the available natural resources in the study area, while the third axis highlights the most important minerals actually being exploited and their use in industry. The study concluded with findings indicating that the study area in the Kurdistan Region of Iraq is characterized by geological and topographical diversity that allows for the presence of metallic minerals such as iron, copper, lead, and zinc, and non-metallic minerals such as limestone, gypsum, and marble. This diversity reflects the importance of mineral resources in supporting industrial planning and enhancing the productive capacity of the industrial sector in the region, with the necessity of considering geographical and geological characteristics to achieve sustainable economic development.